Perbandingan Metode Brainstorming dan Metode Buzz Group dalam Pemberian KIE Kesehatan Reproduksi di Posyandu Remaja Puskesmas Aur Duri Kota Jambi - Ruwayda Ruwayda; Netti Herawati (Jurnal Akademika Baiturrahim Jambi, 2021)
This study aims to analyze the effectiveness of the Brainstorming method and the Buzz Group method in providing IEC for reproductive health at the AurDuri Youth Health Center Posyandu in Jambi City in 2019. This research is a quasi-experimental study using a pretest and posttest design with control group design. The population is all adolescents who visit the posyandu as many as 60 people. Samples were taken using a total sampling technique of 30 treatment groups given the Brainstorming method and 30 people received the Buzz Group method. The research instrument was a questionnaire. Data analysis was carried out univariately to determine the frequency distribution, then bivariate analysis using the dependent t-test to see differences in knowledge before and after giving the brainstorming method and the Buzz Group method. The results showed that there was a difference in the mean increase in respondents' knowledge before and after using the brainstorming method with a mean difference of 1.233 and the difference in knowledge before and after using the buzz group method, namely 3.133. While the results of the analysis of differences in knowledge using the brainstorming method and the buzz group with a p value of 0.000, the difference in the mean value of 2.689 means that the buzz group method is more effective in increasing adolescent knowledge about reproductive health than the brainstorming method. It is suggested that the puskesmas should provide guidance to youth posyandu using a variety of varied methods such as buzz groups in providing IEC for reproductive health